Laparoscopic nephrectomy in crossed-fused inferior ectopic kidneys – Defusing complexities: A case series - Zain Tamboli; Alok Srivastava; Ishwar Ram Dhayal; Sanjeet Singh (Journal of Minimal Access Surgery)
Background: Crossed fused renal ectopia manifests as an operative challenge to the minimally invasive urologist. Provided that certain preset steps are meticulously followed and the anatomy is understood, it is not a difficult task to operate on these cases. Patients and Methods: This is a retrospective study of 15 cases at our Dr. RMLIMS, Lucknow over a period of 5 years. Results: The mean operative time was 117.3 minutes and the mean blood loss was 99.3 ml. Two arteries were encountered in 53.3 % of cases, but they can vary in number from a single artery to even six, as found in our series. Two veins were found in 46.6 % of cases, and even up to four veins can be found. Conclusions: Tackling a case of crossed fused inferior renal ectopia by laparoscopic simple nephrectomy is possible with ease and confidence, provided that certain steps are carefully followed to minimize the possibility of complications and conversion to open surgery.